Comparison between SCB-IFIT, un-notched SCB-IFIT and IDEAL-CT for measuring cracking resistance of asphalt mixtures. (20th August 2020) - Yan, Chuanqi; Zhang, Yuan; Bahia, Hussain U.
Highlights: The un-notched SCB tests can reduce test time and improve test repeatability. IDEAL-CT has a high correlation with SCB-IFIT, but with a lower variation in results. Mixture's cracking resistance index is well related to binder's fatigue behaviour. Abstract: In the last few years two types of tests have been proposed to estimate cracking resistance of asphalt mixtures at intermediate temperatures. The Semi-Circular Bending Illinois Flexibility Index Test (SCB-IFIT) is becoming widely used and it has been accepted as a quality control test in one state. However, the preparation of test specimen for SCB-IFIT is somewhat complicated and requires cutting and notching which could cause unexpected testing variance. In addition, the recently developed indirect tensile asphalt cracking test (IDEAL-CT), which requires no cutting or notching of specimen is also becoming widely considered as a possible practical test. In this paper, the need for the notch in the SCB-IFIT procedure is evaluated. In addition, the IDEAL-CT is compared to the SCB tests with and without notch. The comparison is focused on the specimen preparation, testing set-up, testing variance, and the capability of discriminating between different mixtures. The flexibility index (FI) results from the SCB with and without notch show a strong linear correlation (R 2 of 0.95). The notched specimens have a larger variance in their results than un-notched specimens, indicating that the notch can be eliminated to reduce the variance of results. The cracking tolerance index (CTindex ) results from IDEAL-CT are found to correlate very well with the FI from SCB-IFIT, and CTindex results show less variation than the FI results (average COV of 5.3% versus 23.0%). Since the IDEAL-CT requires no specimen cutting or notching, it could be a promising alternative to evaluate cracking resistance of asphalt mixtures.